Role of MTA1 in Cancer Progression and Metastasis - Sen, Nirmalya (Cancer Metastasis Rev, 2014)
The MTA1 protein contributes to the process of cancer progression and metastasis through multiple genes and protein targets and interacting proteins with roles in transformation, anchorage-independent growth, invasion, survival, DNA-repair, angiogenesis, hormone-independence, metastasis and therapeutic resistance. MTA proteins control a spectrum of cancer promoting processes by modulating the expression of target genes and/or the activity of MTA-interacting proteins. In the case of MTA1, these functions are manifested through post-translational modifications of MTA1 in response to upstream signals, MTA1 interaction with binding proteins and the expression of target gene products. The MTA1 coregulator interacts with nucleosomes through modified histones and is an integrator of extracellular signaling and gene activator. Studies delineating the molecular basis of dual functionality of MTA1 reveal that the functions of MTA1-chromatin modifying complexes in the context of target gene regulation are dynamic in nature. The nature and targets of MTA1-chromatin modifying complexes are also governed by the dynamic plasticity of the nucleosome landscape as well as kinetics of activation and inactivation of enzymes responsible for post-translational modifications on the MTA1 protein. These broadly applicable functions also explain why MTA1 may be a ‘hub’ gene, whose current understanding is limited to selective influences on gene with roles in cancer but further research may reveal a more global influence. Because the deregulation of enzymes and their substrates with roles in MTA1-biology is not necessarily limited to cancer, we speculate that the lessons from MTA1 as a prototype dual master coregulator will be relevant for other human diseases. In this context, the concept of the dynamic nature of corepressor versus coactivator complexes and the MTA1 proteome as a function of time to signal is likely to be generally applicable to other multi-proteins regulatory complexes in living systems.